PENGARUH LATIHAN SEPAK BOLA TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK USIA 5-6 TAHUN - Zamawi, Muhammad Nur Farish (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
This study aims to determine the effect of soccer training on gross motor development of children aged 5-6 years at Dharma Bakti Kindergarten Turipinggir, Jombang Regency.. This research was conducted experimentally by involving educators as collaborators. The research subjects consisted of 12 boys, who were students in group B TK Dharma Bakti. The object of this research is the development of children's gross motor skills through soccer training activities. This research uses a quantitative type approachLike an experimentresearch design